Deep Trade Agreements and Heterogeneous Firms Exports - Matteo Neri-Lainé; Gianluca Orefice; Michele Ruta (Center for Economic Studies and ifo Institute (CESifo), 2023)
This paper studies the effect of regional trade agreements on firms' exports. Using detailed information on the content of trade agreements and firm-level exports for 31 developing countries between 2000 and 2020, the analysis shows that the depth of trade agreements matters for the export performance of firms. Moving from shallow to deep trade agreements boosts firms' exports, on average, by 3.6 percent. In line with models of trade with heterogeneous firms and mark-ups, the trade impact of deep trade agreements depends on the firm's characteristics. The impact is stronger for large firms and firms involved in global value chains and is negative for small firms. Robustness tests, an event study approach and an Instrumental Variable strategy confirm the causal interpretation of the results. These heterogeneous impacts on firms' exports imply a selection (pro-competitive) effect of deep trade agreements with significant welfare consequences for signatory countries.
Keywords: F13; F14; F15; 330; deep trade agreements; exports; firm heterogeneity; developing countries